The Influence of Intellectual Capital and Sustainability Reporting on Company Value with Investment Opportunity Set as Moderating Variables - I Made Widi Hartawan; Desak Nyoman Sri Werastuti; Gede Adi Yuniarta (International Journal of Social Science and Business, 2022)
Currently, countries in the world are entering the era of the industrial revolution 4.0, where information technology is growing and making everything borderless. In this era, innovations and significant changes fundamentally changed the existing system. Change from a system that focuses on empowering the workforce in running a business to a system that focuses on science in running a business. Companies are competing to keep up with the changes that occur to increase the company's value amid growing competition. This study aims to analyze the effect of intellectual capital and sustainability reporting on firm value with the investment opportunity set as a moderating variable in companies that are members of the LQ45 index during the 2018-2020 periods. The sampling method used purposive sampling and obtained a sample of 20 companies with 60 observations. The research data come from annual reports and sustainability reports that companies have published on the Indonesia Stock Exchange and related company websites. The data analysis method uses multiple regression analysis with the help of the Stata 12.0 application. The results showed that intellectual capital had no positive and significant effect on firm value, sustainability reporting had no positive and significant effect on firm value, investment opportunity set was unable to moderate intellectual capital on firm value, and investment opportunity set was unable to moderate sustainability reporting on firm value.